2015
DOI: 10.1002/2014sw001085
|View full text |Cite
|
Sign up to set email alerts
|

Assessing predictive ability of three auroral precipitation models using DMSP energy flux

Abstract: /s, and use this point as a proxy for the equatorward boundary of the auroral oval in a particular MLT sector. We then calculate a prediction efficiency (PE) score by comparing the DMSP boundary coordinates to each model, using the same energy flux threshold to obtain a model's boundary location. We find that the PE for the OVATION Prime model is 0.55, and the PE for the Hardy Kp model is 0.51. When we accomplish the same analysis using a higher energy flux threshold equal to 0.6 erg/cm 2 /s, the OVATION Prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…Lane et al . [] have shown that several empirical models can be reasonably and equally accurate in predicting equatorward boundary of auroral oval in several precipitating electron energy ranges. We would like to note that we compare the total auroral heating as defined from GITM with the hemispheric power.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lane et al . [] have shown that several empirical models can be reasonably and equally accurate in predicting equatorward boundary of auroral oval in several precipitating electron energy ranges. We would like to note that we compare the total auroral heating as defined from GITM with the hemispheric power.…”
Section: Discussionmentioning
confidence: 99%
“…Despite possible underestimation of hemispheric power, the model equation (1) can be very useful for providing upper boundary conditions for global circulation models run in a forecasting mode. Lane et al [2015] have shown that several empirical models can be reasonably and equally accurate in predicting equatorward boundary of auroral oval in several precipitating electron energy ranges. We would like to note that we compare the total auroral heating as defined from GITM with the hemispheric power.…”
Section: 1002/2017sw001650mentioning
confidence: 99%
“…7 and 11). Statistical analysis based on 28 days of DMSP satellite energy flux measurements shows that OP can accurately describe the location of the auroral oval's equatorward boundary (Lane et al 2015). Auroral electron precipitation is expected to occur near upward R1, especially during intervals of IMF B z < 0 (Ohtani et al 2010;Korth et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…When calculating the auroral precipitation, OVATION Prime accounts for several different auroral types (i.e., diffuse aurora, monoenergetic, broadband, and ion), seasonal variations, and the magnetic latitude (MLAT) and magnetic local time (MLT) of each of its modeled bins (which are 0.5° in MLAT by 0.25°, or 1 min, in MLT in size). All of which ensures that it is often more accurate at modeling the auroral oval than other real‐time models [ Newell et al , ; Lane et al , ] and can reliably predict when an aurora will be visible [ Machol et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…While both OP10 and OP13 have been validated and found to provide reasonable estimates of the location and intensity of the aurora [e.g., Machol et al , ; Newell et al , ; Lane et al , ], no extensive testing has yet been performed on the accuracy of the SWPC forecast product or the location of the view line.…”
Section: Introductionmentioning
confidence: 99%